"... the real war will never get in the books" : selections from writers during the Civil War - Masur, Louis P. (Oxford University Press, 1995)
Drawing on a wide range of material, including diaries, letters, and essays, this book captures the reactions, as the American Civil War was waged, of writers such as Nathaniel Hawthorne, Harriet Beecher Stowe, Ralph Waldo Emerson, Frederick Douglass, Herman Melville, Walt Whitman, Henry Adams, and Louisa May Alcott.